Peningkatan Produksi Bawang Merah (Allium asclonicum L.) Akibat Pemberian NPK Fermentasi Berbagai Jenis Limbah Tanaman - Sitepu, Sri Mahareni; Refnizuida, Refnizuida (UNIVERSITAS LABUHANBATU, 2023)
Shallot is a horticultural commodity that has high economic value and has good market prospects because it contains high nutrition and can be used as spices and ingredients for traditional medicine. However, shallot production in Indonesia still often fluctuates and even experiences a shortage in meeting the needs of domestic consumers. To increase shallot production, this can be done through intensification efforts, namely by improving cultivation techniques, including the use of organic fertilizers, proper fertilization, and the use of superior varieties. This study used a factorial randomized block design consisting of 2 treatment factors, namely factor I was fermented NPK (F) consisting of 0 ml, 250 ml, 500 ml and 750 ml. Factor II was the variety (V) of the Brebes Bima variety, the Probolinggo variety and the Nganjuk variety. The data analysis method was a factorial randomized block design (RBD). The results showed that the application of fermented NPK and the use of varieties had a very significant effect on the number of tillers per clump (saplings), production per sample (g), production per plot (g), tuber diameter (mm).Keywords: shallots, NPK fermented products, varietyÂ